Análisis de la estructura de mercado de la industria del banano - Domínguez, J.M. (2009)
This paper presents an analysis of the cost structure of production of the banana industry in Ecuador, focusing on the relationship between producers and exporters of the fruit. The government has intervened since last decade in the banana sector trying to encourage the production and trade of bananas. But there is a great divergence regarding the choice of the minimum price and the lack of a price control system. Therefore, It is necessary to understand the structure that follows the banana market. This study will also provide the methodology in order to estimate the marginal cost function of the banana production in Ecuador with the ITSUR method by using the available information. With this estimation we will be able to quantify the impact of variations of the inputs and the labor costs into the final product price. With the results obtained from this estimation and after the analysis of their behavior. It would be possible to think in suggestions in order to balance market forces and to encourage avoiding